Highly Active Ni- and Co-Based Bimetallic Catalysts for Hydrogen Production From Ammonia-Borane - Furukawa, Shinya (Front Chem, 2019)
Ammonia-borane is one of the most promising candidates for hydrogen carriers. A series of Ni- and Co-based bimetallic catalysts supported on SiO(2) (Ni–M/SiO(2) and Co–M/SiO(2); M = Ga, Ge, Sn, Zn) was prepared and tested as catalysts for hydrogen production from ammonia-borane (AB) in water or methanol. Ni–Zn/SiO(2) and Co–Ge/SiO(2) exhibited catalytic activities much higher than those of monometallic Ni/SiO(2) and Co/SiO(2), respectively. Ni–Zn/SiO(2) showed a high catalytic activity when water was used as a solvent, where the reaction was completed within 6 min at room temperature with a specific reaction rate of 4.3 ml min(−1) mmol-cat(−1) mM-AB(−1). To the best of our knowledge, this is the highest value among those reported using 3d metal-based catalysts. Co–Ge/SiO(2) afforded a five-fold higher reaction rate than that of the corresponding monometallic Co/SiO(2). XRD, TEM, and HAADF-STEM-EDS analyses revealed that Ni(0.75)Zn(0.25) and Co(0.8)Ge(0.2) solid-solution alloys were formed with high phase purities. An XPS study showed that Co atoms in Co(0.8)Ge(0.2) were electron-enriched due to electron transfer from Ge to Co, which may be the origin of the improved catalytic activity.